We Need the Largest Experiments on Earth to Achieve Our Climate Targets - Bronson W. Griscom; Susan C. Cook‐Patton; Erin Sills; Kelsey Jack; Thomas W. Crowther; Sebastien Costedoat; Christopher Field; David Hole; Lisa M. McCullough; Subhrendu K. Pattanayak; Sassan Saatchi; Will R. Turner (Global Change Biology, 2025)

New opportunities and challenges for conservation evidence synthesis from advances in natural language processing - Charlotte H. Chang; Susan C. Cook‐Patton; James T. Erbaugh; Luci Lu; Yuta J. Masuda; István Molnár; Dávid Papp; Brian E. Robinson (Conservation Biology, 2025)
Addressing global environmental conservation problems requires rapidly translating natural and conservation social science evidence to policy‐relevant information. Yet, exponential increases in scientific production combined with disciplinary differences in reporting research make interdisciplinary evidence syntheses especially challenging. Ongoing developments in natural language processing (NLP), such as large language models, machine learning (ML), and data mining, hold the promise of accelerating cross‐disciplinary evidence syntheses and primary research. The evolution of ML, NLP, and artificial intelligence (AI) systems in computational science research provides new approaches to accelerate all stages of evidence synthesis in conservation social science. To show how ML, language processing, and AI can help automate and scale evidence syntheses in conservation social science, we describe methods that can automate querying the literature, process large and unstructured bodies of textual evidence, and extract parameters of interest from scientific studies. Automation can translate to other research agendas in conservation social science by categorizing and labeling data at scale, yet there are major unanswered questions about how to use hybrid AI‐expert systems ethically and effectively in conservation.

Quantifying the Effect Size of Management Actions on Aboveground Carbon Stocks in Forest Plantations - Cyril H. Melikov; Jacob J. Bukoski; Susan C. Cook-Patton; Hongyi Ban; Jessica L. Chen; Matthew D. Potts (Current Forestry Reports, 2023)
Purpose of the Review Improved forest management is a promising avenue for climate change mitigation. However, we lack synthetic understanding of how different management actions impact aboveground carbon stocks, particularly at scales relevant for designing and implementing forest-based climate solutions. Here, we quantitatively assess and review the impacts of three common practices—application of inorganic NPK fertilizer, interplanting with N-fixing species, and thinning—on aboveground carbon stocks in plantation forests. Recent Findings Site-level empirical studies show both positive and negative effects of inorganic fertilization, interplanting, and thinning on aboveground carbon stocks in plantation forests. Recent findings and the results of our analysis suggest that these effects are heavily moderated by factors such as species selection, precipitation, time since practice, soil moisture regime, and previous land use. Interplanting of N-fixing crops initially has no effect on carbon storage in main tree crops, but the effect becomes positive in older stands. Conversely, the application of NPK fertilizers increases aboveground carbon stocks, though the effect lessens with time. Moreover, increases in aboveground carbon stocks may be partially or completely offset by emissions from the application of inorganic fertilizer. Thinning results in a strong reduction of aboveground carbon stocks, though the effect lessens with time. Summary Management practices tend to have strong directional effects on aboveground carbon stocks in plantation forests but are moderated by site-specific management, climatic, and edaphic factors. The effect sizes quantified in our meta-analysis can serve as benchmarks for the design and scoping of improved forest management projects as forest-based climate solutions. Overall, management actions can enhance the climate mitigation potential of plantation forests, if performed with sufficient attention to the nuances of local conditions.

Large climate mitigation potential from adding trees to agricultural lands - Melissa Chapman; Wayne S. Walker; Susan C. Cook‐Patton; Peter W. Ellis; Mary Farina; Bronson W. Griscom; Alessandro Baccini (Global Change Biology, 2020)
While improved management of agricultural landscapes is promoted as a promising natural climate solution, available estimates of the mitigation potential are based on coarse assessments of both agricultural extent and aboveground carbon density. Here we combine 30 meter resolution global maps of aboveground woody carbon, tree cover, and cropland extent, as well as a 1 km resolution map of global pasture land, to estimate the current and potential carbon storage of trees in nonforested portions of agricultural lands. We find that global croplands currently store 3.07 Pg of carbon (C) in aboveground woody biomass (i.e., trees) and pasture lands account for an additional 3.86 Pg C across a combined 3.76 billion ha. We then estimate the climate mitigation potential of multiple scenarios of integration and avoided loss of trees in crop and pasture lands based on region‐specific biomass distributions. We evaluate our findings in the context of nationally determined contributions and find that the majority of potential carbon storage from integration and avoided loss of trees in crop and pasture lands is in countries that do not identify agroforestry as a climate mitigation technique.

Tree diversity promotes growth of late successional species despite increasing deer damage in a restored forest - John L. Devaney; Jamie Pullen; Susan C. Cook‐Patton; Karin T. Burghardt; John D. Parker (Ecology, 2020)
The role of tree diversity in restored forests and its impact on key ecological processes like growth and resistance to herbivory has become increasingly important. We analyzed height growth and white‐tailed deer Odocoileus virginianus browsing damage to saplings of 16 broadleaved tree species in a large‐scale (13 ha) reforestation experiment in Maryland, USA, where we manipulated tree diversity in 70 1,225‐m 2 plots. After four growing seasons, higher plot‐level tree richness led to increased deer browsing damage (i.e., associational susceptibility). Despite increased deer damage to saplings in mixed plots, tree richness had no overall effect on sapling height growth. However, diversity–height relationships were related to species functional traits. Light demanding species with large leaves and faster growth rates had reduced heights in mixtures, whereas shade‐tolerant, slower‐growing species generally had either increased or unchanged height growth in diverse tree communities, likely related to increased canopy closure in mixtures relative to monocultures. We show that tree diversity can improve growth of late successional species despite exacerbated mammalian herbivore damage. By facilitating the establishment of species with a range of life‐history strategies, increased tree diversity may enhance ecosystem multi‐functionality in the early stages of forest restoration.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

We need both natural and energy solutions to stabilize our climate - Bronson W. Griscom; Guy Lomax; Timm Kroeger; Joseph E. Fargione; Justin Adams; Lucy Almond; Deborah Bossio; Susan C. Cook‐Patton; Peter W. Ellis; Christina M. Kennedy; Joseph Kiesecker (Global Change Biology, 2019)

Integrating physiological threshold experiments with climate modeling to project mangrove species’ range expansion - Kyle C. Cavanaugh; John D. Parker; Susan C. Cook‐Patton; Ilka C. Feller; A. Park Williams; James R. Kellner (Global Change Biology, 2015)
Predictions of climate‐related shifts in species ranges have largely been based on correlative models. Due to limitations of these models, there is a need for more integration of experimental approaches when studying impacts of climate change on species distributions. Here, we used controlled experiments to identify physiological thresholds that control poleward range limits of three species of mangroves found in North America. We found that all three species exhibited a threshold response to extreme cold, but freeze tolerance thresholds varied among species. From these experiments, we developed a climate metric, freeze degree days ( FDD ), which incorporates both the intensity and the frequency of freezes. When included in distribution models, FDD accurately predicted mangrove presence/absence. Using 28 years of satellite imagery, we linked FDD to observed changes in mangrove abundance in Florida, further exemplifying the importance of extreme cold. We then used downscaled climate projections of FDD to project that these range limits will move northward by 2.2–3.2 km yr −1 over the next 50 years.

Neighbours matter: natural selection on plant size depends on the identity and diversity of the surrounding community - Amy L. Parachnowitsch; Susan C. Cook-Patton; Scott H. McArt (Evolutionary Ecology, 2014)

Exotic plants contribute positively to biodiversity functions but reduce native seed production and arthropod richness - Susan C. Cook-Patton; Anurag A. Agrawal (Ecology, 2014)
Although exotic plants comprise a substantial portion of floristic biodiversity, their contributions to community and ecosystem processes are not well understood. We manipulated plant species richness in old‐field communities to compare the impacts of native vs. exotic species on plant biomass, seed production, and arthropod community structure. Plants within diverse communities, regardless of whether they were native or exotic, had higher biomass and seed production than in monocultures and displayed positive complementarity. Increasing native or exotic plant richness also enhanced the richness of arthropods on plants, but exotics attracted fewer arthropod species for a given arthropod abundance than did natives. Additionally, when exotic and native plants grew together, exotics suppressed seed production of native species. Thus, exotic plants appear to contribute positively to some biodiversity functions, but may impact native communities over longer time frames by reducing native seed production and recruiting fewer arthropod species.

Relationships between arthropod richness, evenness, and diversity are altered by complementarity among plant genotypes - Scott H. McArt; Susan C. Cook-Patton; Jennifer S. Thaler (Oecologia, 2012)